Aspirin and risk of multiple myeloma in adults: A systematic review and meta-analysis. (2017) - Lee, Shing Fung; Ng, Ting Ying; Wong, Frank Chi Sing; Tung, Stewart Yuk
Abstract: Multiple myeloma is a relatively uncommon plasma cell malignancy. Preclinical and clinical studies have suggested that aspirin might modify the risk of multiple myeloma. We performed a systematic review and meta-analysis of studies to examine the association between regular aspirin use and risk of multiple myeloma. Five observational studies including 332, 660 adults were evaluated. The pooled estimate had a hazard ratio of 0.90 (95% confidence interval =0.58−1.39; P=0.638). Odds ratios from the two case-control studies were similar. The findings demonstrated that there was no significant association between aspirin use and the risk of multiple myeloma. Highlights: This is a systematic review of aspirin use on the incidence risk of multiple myeloma. There is no evidence that aspirin modifies the risk of multiple myeloma. More studies are needed to assess the impact of aspirin on the risk of multiple myeloma.